ANALYSIS OF RISK PROFILE, EARNINGS, AND CAPITAL ON THE HEALTH LEVEL OF CENTRAL ASIA BANK - Viane Talundu; Vitayanti Fattah; Muslimin; Fera (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Banking plays a crucial role in supporting national economic growth through its intermediary function, liquidity provision, and credit distribution to the real sector. During the monetary policy normalization period of 2022–2024, the banking industry faces the challenge of maintaining optimal credit distribution without neglecting risk control and capital strengthening. This situation emphasizes the importance of evaluating bank health, both empirically and based on relevant theoretical frameworks. This study aims to analyze the health level of PT Bank Central Asia Tbk based on Risk Profile, Earnings, and Capital aspects , and examine the results from the perspectives of Risk Management Theory, Efficiency Theory, and Trade-Off Theory . The study uses a descriptive quantitative approach with secondary data in the form of financial reports for the 2022–2024 period. The indicators analyzed include Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA), Net Interest Margin (NIM), and Capital Adequacy Ratio (CAR) in accordance with the provisions of the Financial Services Authority (OJK). The research results show that BCA is in the Very Healthy (PK-1) category, with an achievement level of 96.00%–100.00%. Credit growth was not accompanied by an increase in credit risk, profitability increased consistently, and capital remained well above the minimum threshold. These findings demonstrate that the balance between credit growth, risk management, and capital adequacy is key to maintaining banking stability during the economic recovery period.